PDL1-dependent trans-acting siRNAs regulate lateral organ polarity development in rice - Zhang, Yi; You, Jing; Tang, Jun; Xiao, Wenwen; Wei, Mi; Wu, Ruhui; Liu, Jinyan; Zong, Hanying; Zhang, Shuoyu; Qiu, Jie; Chen, Huan; Ling, Yinghua; et al. (Journal of Integrative Agriculture, 2025)
•The pdl1 mutant exhibits twisted leaves and malformed floral organs due to disrupted adaxial–abaxial polarity.•PDL1 encodes a cytoplasmic located SGS3 protein, which regulates tasiR-ARF synthesis to modulate OsARFs, while elevating abaxial miR165/166 and repressing adaxial OSHBs. Leaves and glumes act as lateral organs and have essential effects on photosynthesis and seed morphology, thus affecting yield. However, the molecular mechanisms controlling their polarity development in rice still need further study. Here, we isolated a polarity defect of lateral organs 1 (pdl1) mutant in rice, which exhibits twisted/filamentous-shaped leaves and cracked/filamentous-shaped lemmas caused by defects in polarity development. PDL1 encodes a SUPPRESSOR OF GENE SILENCING 3 protein localized in the cytoplasmic granules. PDL1 is expressed in the shoot apical meristem, inflorescence meristem, floral meristem, and lateral organs including leaves and floral organs. PDL1 is involved in the synthesis of tasiR-ARF, which may subsequently modulate the expression of OsARFs. Meanwhile, the expression levels of abaxial miR165/166 and the adaxial identity genes OSHBs were respectively increased and reduced significantly. The results of this study clarify the molecular mechanism by which PDL1-mediated tasiR-ARF synthesis regulates the lateral organ polarity development in rice.